Images of the West in Urban Indonesia: Muslims Negotiating the Western Path to Modernity - Melanie V. Nertz (UIN Sunan Gunung Djati Bandung, 2013)
Islamic fundamentalism and terrorism is unjustified. In fact, the political change after 1998 and the increasing influence of religion combined with an intensified process of globalization have led to socio-cultural vicissitudes inIndonesia beyond which we can only estimate what future patterns of orientation the population will have. Based on data from informal conversations, interviews and participant observation, it will be argued that, notwithstanding considerable variations, Muslim Indonesians uphold not solely negative but ambivalent images of the West and that in comparison with and opposition to the „Self‟ or „Own‟ the West is examined as one of many frames of reference by which modernity is negotiated and can be put into practice. Many interlocutors overcame the binary of East and West by envisioning that Indonesia could combine the advantages of both, the Own and the Foreign in order to step into a desirable future.